Regulatory T cell profiles in patients with N-methyl-ᴅ-aspartate receptor-antibody encephalitis - Iro, MA; Rollier, CS; Irani, SR; Sadarangani, M; Al-Diwani, A; Pollard, AJ; Clutterbuck, EA (Korean Encephalitis and Neuroinflammation Society, 2023)
Purpose Purpose Regulatory T cells (Tregs) have been implicated in the pathogenesis of several autoimmune disorders and used in adoptive cell transfer therapies. Neither have been explored in patients with autoimmune encephalitis where treated patient outcomes remain suboptimal with frequent relapses. Here, to identify new treatment strategies for autoimmune encephalitis, we sought to evaluate the proportion of circulating Tregs and Treg subpopulations in peripheral blood of patients with N-methyl-ᴅ-aspartate receptor-antibody encephalitis (NMDAR-Ab-E) and compared this with healthy controls. Methods We compared the phenotype of peripheral blood Tregs in four adult NMDAR-Ab-E patients and four age- and sex-matched healthy controls using an 11-color flow cytometry assay panel for characterization of Tregs (CD4+ CD25+ FoxP3+) cells into naïve (chemokine receptor [CCR] 7+ CD45RA+), central memory (CCR7+ CD45RA–), and effector memory (CCR7– CD45RA–) cells. We also examined and compared the expression of the CCR6 by circulating Tregs and the respective Treg subpopulations between the study groups. Results The proportion of circulating Tregs was similar between patients with NMDAR-Ab-E and healthy controls but the proportion of naïve Tregs was lower in NMDAR-Ab-E patients (p = 0.0026). Additionally, the frequency of circulating effector memory Tregs was higher, and the proportion of circulating effector memory Tregs expressing CCR6 was lower, in NMDAR-Ab-E patients compared with healthy controls (p = 0.0026). Conclusion Altered Treg homeostasis may be a feature of patients with NMDAR-Ab-E. Future studies with larger samples are warranted to validate these findings.